EFFECT OF FLY ASH ON GEOTECHNICAL PROPERTIES OF SOIL - Dixit, Abhishek; Nigam, Manish; Mishra, Rahul (International Journal of Engineering Technologies and Management Research, 2016)
This paper investigates the effect of fly ash (generated from thermal power plant, Panki, Kanpur) on geotechnical properties of local soil, Bhauti Kanpur (U.P), INDIA. The fly ash used in the experimental work was of Class ‘F’ and soil was clayey in nature .Fly ash collected from the hopper attached to an electrostatic precipitator when coal was changed at a coal fired power plant. Concerning the major challenges regarding the safe reuse, management and disposal of these wastes an attempt has been made to mix fly ash at 5,10, 15, 20, 25, and 30% on the basis of dry weight with local clay soil. To understand the behavior of fly ash with soil, numbers of laboratory experiments were performed on the local soil (clay) and contaminated soil with varying percentage of fly ash. As the result, it is shown that all the investigated properties were decreased except CBR value and optimum moisture content.